Bluetooth wireless technology low profile printed antenna - Hamid, M.R. (2003)
Bluetooth wireless technology provides short-range wireless voice and data communication in the industrial, scientific and medical (ISM) band of radio spectrum. This paper describes several half wave printed dipole antennas with offset feed operating at Bluetooth frequency of 2.45 GHz. Two variation of feeding techniques have been employed, namely the side feed and direct feed. Direct feed techniques were incorporated in some structures in order to reduce antennas size. A corresponding rectangular patch antenna operating at the same frequency is also designed for comparison purposes. Numerical simulations have been carried out on the designed structures using micropatch and Sonnetlite softwares. The antennas have been fabricated on GML laminates and tested. Measured one port results showed that all the antennas are well-matched at their corresponding frequency of operation. The co-polarisation radiation patterns exhibit broad beamwidths.